Digital Menus and Customer Revisit Intentions: Insights from Klang Valley Restaurants Using an Extended TAM Framework - Nur Izzati Ghazali; Rahayu Othman; Norzaidah Ngali; Norazlina Rahmat; Maisara Zainal Abidin (Information Management and Business Review, 2025)
The study investigates the effect of digital menus on customers' revisit intention to restaurants within Klang Valley, employing the Technology Acceptance Model (TAM). Although digital menus improve convenience by enabling customers to explore options and access information, challenges such as privacy concerns and usability, especially for the elderly, remain prevalent. A quantitative study online was conducted with 122 respondents who had experience using digital menus at various restaurants in Klang Valley. This study examined consumer acceptance about perceived security, usefulness, ease of use, and enjoyment, and how these factors affect their tendency to return. The study demonstrates that perceived enjoyment significantly affects intentions to revisit, although security, usefulness, and ease of use do not. This indicates that customer satisfaction is primarily influenced by the enjoyment derived from the ordering experience rather than practical considerations. Future research should identify ways to improve the digital dining experience, particularly for individuals facing usability difficulties.